Formulación de un Plan para la Implementación del Sistema de Ingresadores de Estadísticas Operativas para el Transporte de Pasajeros en Autobús en la ARESEP - Jiménez-Cordero, Christian (Instituto Tecnológico de Costa Rica, 2013)
The work included analysis of the characteristics of the new system for recording operational reports is to be implemented by the Transport Services Division (DITRA) of ARESEP, along with the analysis of environmental characteristics and organization itself. From the analysis of strengths, weaknesses, opportunities and threats of these three factors (system, organization and environment) defines a series of strategic actions in order to identify critical factors that influence the successful implementation of the new system. Based on the results of strategic analysis, implementing project management methodology of PMI in order to build an action plan to guide both project managers as the leadership of the DITRA, to define priorities and commit the financial and personnel resources necessary for the smooth implementation of the plan. The study concludes by proposing an action plan to develop while emphasizing the importance of providing proper monitoring and control over it to achieve the objectives with the implementation of the new system.
Proyecto de Graduación (Maestría en Gerencia de Proyectos). Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos. Escuela de Administración de Empresas, 2011.
Keywords: Administración; Análisis de proyectos; Plan de acción; Evaluación de proyectos